Rancang Bangun Sistem Informasi Kepegawaian Berbasis Web di STIE Kesatuan - Yanto Hermawan; Ade Mulyana; Nurul Fadillah Rizky I. (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2019)
STIE Kesatuan personnel information system is a problem of special concern in IBI Kesatuan HRD. This is with the ease and effectiveness in processing employee data such as employee data entry, editing employee data, searching employee data, reporting employee data either on screen or printed on paper. There are still many STIE Kesatuan who have not filled in data on manual paper, such as employees who have to fill out a leave form and wait for approval. So to overcome this we need a personnel information system that is better than the previous system, for now the employee information is only from Microsoft Excel and manual data. This study uses a system design implemented with the Diagram Unified Modeling Language (UML). The expected end result is that the employee web-based information system can solve system problems that run more optimally in the employee data entry process. With this research, it is hoped that it can help IBI Kesatuan, especially HRD, to develop a management information system. Keywords: Information Systems, UML Diagram.